2013
DOI: 10.2106/jbjs.l.00901
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Erythromycin and Colistin-Loaded Cement in Total Knee Arthroplasty Does Not Reduce the Incidence of Infection

Abstract: The use of erythromycin and colistin-loaded bone cement in total knee arthroplasty did not lead to a decrease in the rate of infection when systemic prophylactic antibiotics were used, a finding that suggests that the use of antibiotic-loaded bone cement would not be indicated in the general population. Further research is needed to assess whether its use is recommended for patients with a higher risk of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 26 publications
3
74
1
1
Order By: Relevance
“…However, the rate of infection in the control arms was high in both studies, 13.5% in the diabetics and 3.1% in the nondiabetics, limiting the generalizability of these results to populations with lower rates of infection. A larger study that randomized 2,948 patients undergoing primary knee arthroplasty to receive erythromycin-and colistin-loaded PMMA or plain PMMA found no difference in the deep infection rates at 1 year (47). As acknowledged by the authors of that study, these results cannot be generalized to other, more frequently used antimicrobials.…”
Section: Antimicrobial-loaded Pmma At Prosthesis Implantationmentioning
confidence: 80%
See 2 more Smart Citations
“…However, the rate of infection in the control arms was high in both studies, 13.5% in the diabetics and 3.1% in the nondiabetics, limiting the generalizability of these results to populations with lower rates of infection. A larger study that randomized 2,948 patients undergoing primary knee arthroplasty to receive erythromycin-and colistin-loaded PMMA or plain PMMA found no difference in the deep infection rates at 1 year (47). As acknowledged by the authors of that study, these results cannot be generalized to other, more frequently used antimicrobials.…”
Section: Antimicrobial-loaded Pmma At Prosthesis Implantationmentioning
confidence: 80%
“…Some of these factors include male gender (6,8,20,36,46,47), smoking (21), antecedent bacteremia (during the previous year) (48), and antecedent septic arthritis of the index joint (26). The biological plausibility for some of these factors, such as gender, is uncertain.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…69 However, multiple other studies have shown that bone cement loaded with antibiotics did not significantly reduce infection rates. 70,71 Therefore, it is still unclear whether the traditional method of loading bone cement with antibiotics effectively reduces the infection rate following arthroplasty. However, the number of resistant bacterial strains is currently increasing, and if effective measures are not taken, incurable infectious diseases and small wounds may lead to death.…”
Section: Bone Cementmentioning
confidence: 99%
“…Studies have demonstrated a significant reduction in infection rates using antibiotic-impregnated cement in total hip arthroplasty and total knee arthroplasty patient populations (15,16). Conversely, other studies indicated limited clinical benefit, albeit with various antibiotics and concentrations (17,18) and poor descriptions of elution kinetics (19). Additionally, once the antibiotics have eluted from a nonabsorbable cement, the surface becomes a foreign body that is subject to bacterial colonization and biofilm formation (20,21).…”
mentioning
confidence: 99%